Meta-analysis of KRAS mutations and survival after resection of colorectal liver metastases. Issue 10 (21st July 2015) - Brudvik, K W; Kopetz, S E; Li, L; Conrad, C; Aloia, T A; Vauthey, J-N
Abstract: Background: In patients with advanced colorectal cancer, KRAS mutation status predicts response to treatment with monoclonal antibody targeting the epithelial growth factor receptor (EGFR). Recent reports have provided evidence that KRAS mutation status has prognostic value in patients with resectable colorectal liver metastases (CLM) irrespective of treatment with chemotherapy or anti-EGFR therapy. A meta-analysis was undertaken to clarify the impact of KRAS mutation on outcomes in patients with resectable CLM. Methods: PubMed, Embase and Cochrane Library databases were searched systematically to identify full-text articles reporting KRAS -stratified overall (OS) or recurrence-free (RFS) survival after resection of CLM. Hazard ratios (HRs) and 95 per cent c.i. from multivariable analyses were pooled in meta-analyses, and a random-effects model was used to calculate weight and overall results. Results: The search returned 355 articles, of which 14, including 1809 patients, met the inclusion criteria. Eight studies reported OS after resection of CLM in 1181 patients. The mutation rate was 27·6 per cent, and KRAS mutation was negatively associated with OS (HR 2·24, 95 per cent c.i. 1·76 to 2·85). Seven studies reported RFS after resection of CLM in 906 patients. The mutation rate was 28·0 per cent, and KRAS mutation was negatively associated with RFS (HR 1·89, 1·54 to 2·32). Conclusion: KRAS mutation status is a prognostic factor in patients undergoing resection of colorectal liver metastases and should be considered in the evaluation of patients having liver resection. Abstract : Mutations related to negative prognosis